Perbedaan Fungsi Sistolik Ventrikel Kanan antara Hipertensi Arteri Pulmonal dan Hipertensi Vena Pulmonal - Rayhansyah, Vito; Yanni, Mefri; Irramah, Miftah; Hamdani, Rita; Revilla, Gusti; Linosefa, Linosefa (Fakultas Kedokteran Universitas Trisakti, 2025)
Background Pulmonary arterial hypertension (PAH) and pulmonary venous hypertension (PVH) are both associated with increased right ventricular (RV) afterload, potentially leading to RV systolic dysfunction. Despite its prognostic value in predicting right heart failure (RHF), echocardiographic evaluation of RV function remains underutilized in the routine assessment of patients with PAH and PVH. Methods This study aims to evaluate differences in RV systolic function between PAH and PVH patients. A total of 116 patients (58 PAH and 58 PVH) were selected through consecutive sampling from medical records at RSUP Dr. M. Djamil Padang. Echocardiographic parameters were analyzed using appropriate statistical tests based on data distribution and type, including Chi-square, Fisher’s exact, and Mann-Whitney U tests. Results Significant differences were observed between PAH and PVH groups in terms of tricuspid regurgitation (TR) severity (p = 0.003), tricuspid annular plane systolic excursion (TAPSE) (p = 0.013), and tissue Doppler-derived systolic velocity of the tricuspid annulus (S′) (p = 0.001). No significant differences were found in ejection fraction (EF), systolic pulmonary artery pressure (sPAP), mean pulmonary artery pressure (mPAP), or TR velocity (TR Vmax). Overall, RV systolic function differed significantly between the PAH and PVH groups (p = 0.006). Conclusions The findings demonstrate a statistically significant difference in RV systolic function between patients with PAH and PVH. These results underscore the need for more comprehensive and routine echocardiographic evaluation of RV function in these populations to enhance risk stratification and management.